2019
DOI: 10.1371/journal.pone.0210038
|View full text |Cite
|
Sign up to set email alerts
|

Which brain lesions produce spasticity? An observational study on 45 stroke patients

Abstract: Spasticity is an important barrier that can hinder the restoration of function in stroke patients. Although several studies have attempted to elucidate the relationship between brain lesions and spasticity, the effects of specific brain lesions on the development of spasticity remain unclear. Thus, the present study investigated the effects of stroke lesions on spasticity in stroke patients. The present retrospective longitudinal observational study assessed 45 stroke patients using the modified Ashworth Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…To meet the objectives of this study, only a homogenous group of ischemic stroke patients were included, and those with intracerebral hemorrhage and bilateral brain lesions were excluded, as was carried out by previous VLSM studies [ 16 , 18 , 21 ]. The edema and brain shifting in the former group and the more severe neurological deficits in the latter group can mislead VLSM analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the objectives of this study, only a homogenous group of ischemic stroke patients were included, and those with intracerebral hemorrhage and bilateral brain lesions were excluded, as was carried out by previous VLSM studies [ 16 , 18 , 21 ]. The edema and brain shifting in the former group and the more severe neurological deficits in the latter group can mislead VLSM analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Voxel-based lesion-symptom mapping is a neuroimaging technique that can be used to study the relationship between tissue damage and behavior on a voxel-by-voxel basis. VLSM has been widely used to identify lesion-symptom relationships in stroke patients, and has been used extensively to study, among other functions, language [ 16 ], gait [ 17 ], and spasticity [ 18 ]. A recent study a recent study by Suntrup-Krueger et al [ 19 ] demonstrated via VLSM the role of specific cortical lesions with impaired RC in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects were excluded if they had any other functional or structural brain disorder. Similarly, to previous studies for brain lesion analysis, we included the patients with stroke, regardless of type; ischemic and hemorrhagic (1315). Of the 214 individuals who underwent language assessment for aphasia after stroke, 31 qualified for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Only voxels indicating that at least 10% ( n = 3) of the patients had lesions were included in the final analysis. The non-parametric Brunner–Munzel test for continuous data was used (15). Colored VLSM maps representing the z statistics were generated and overlaid onto the automated anatomical labeling and Johns Hopkins University white matter templates provided with the MRIcron software (18, 21).…”
Section: Methodsmentioning
confidence: 99%
“…The same group also found that in 98% of subjects with PSS, velocity-dependent increase in muscle tone in one joint was evident at about 6 weeks post-stroke. Beside identified early clinical signs that predict PSS (velocity-dependent increase in muscle tone in two or more joints, severe paresis and loss of function resulting in severe disability/loss of ADL), recent studies showed that brain lesions involving the basal ganglia, thalamus, insula, and white matter tracts especially the internal capsule, corona radiata, external capsule, and superior longitudinal fasciculus are also predictive for PSS when lesion load is compromising the corticospinal tract (Wissel et al 2015;Lee et al 2019).…”
Section: Introductionmentioning
confidence: 99%